Motivasi Memakai Cadar dalam Perspektif Hukum Syariah pada Mahasiswi IAIN Padangsidimpuan - Sylvia Kurnia Ritonga (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The phenomenon of the veil in the community remains an interesting study because there are still many people who feel foreign to seeing women using it. Negative stigma is often directed at women who wear the veil by considering them as adherents of radicalism, terrorism, and followers of deviant studies. However, this development cannot be dammed and stopped so there are still many female students who wear the veil. The purpose of this study was to determine the motivation to use the veil among female students of IAIN Padangsidimpuan. This research is qualitative descriptive research that is revealing the phenomenon of the veil which is then reviewed from the point of view of Islamic law. Data collection techniques in this study use observation techniques, interviews, and documentation. The data analysis technique used the Miles and Huberman model data triangulation technique, namely data collection, data presentation, and conclusion drawing/verification. The results of this study indicate that the motivation to wear the veil among IAIN Padangsidimpuan students is intrinsic motivation, namely encouragement that comes from within. Extrinsic motivation is classified as little because having experience has a special relationship with